Allometric correlation in Hylocereus costaricensis y H. monocanthus (pitahaya): a tool to quantify growth - Garbanzo-León, Gabriel (2019)
Introduction. Dragon fruit plant (Pitahaya) is a cactacea family plant, it grows naturally in dead trees or stakes in seasonally dry areas, and it has an out-of-order architecture in the growth for being and epiphyte and hemiepiphyte plant, its green steams are structures that play the role of steam-leaf. Currently, in Costa Rica, there is little information on the growth and quantification of dragon fruit morphometry. Objective. The objective of this work was to relate non-destructive variables with destructive variables to develop a useful tool for the use growth projections in dragon fruit in Costa Rica. Materials and methods. The study was carried from 2016 to 2017. Stems from plants sown in soil and substrates were randomly sampled. The following were evaluated: longitude, basal, medium and apical thickness (A), leaf area (indirect method) and biomass (fresh weight, dry weight and moisture percentaje) for each stem. A database was built and it’s linear regressions were calculated, and the site variability (clay soil, loam soil and nurseries) was compared with Kruskal Wallis (α=0.05) test. Results. Linear regressions showed highly significant correlation (r2= 0.97) with the significative correlation (r2=0.85) with dry weight and that the longitude by width presented a foliar area. Two mathematical criteria were determined, to generate better fit equation for more accurate projections of variables. The weight showed significative differences (α=0.01) according to stem growth sites. Conclusion. Linear regression showed high precision (r2= 0.85) in some growth variables in dragon fruit steams, wich could be an effective tool to generate crop growth quantification.